2021
DOI: 10.1186/s12957-021-02220-7
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of modified radical mastectomy with nipple-areola preservation combined with stage I prosthesis implantation using air cavity-free suspension hook in patients with breast cancer

Abstract: Background Mastoscopic surgery is proven to have lower incidence of postoperative complications and better postoperative recovery than traditional breast cancer surgery. This study aimed to examine the feasibility of mastoscopic modified radical mastectomy (MRM) with skin nipple-areola preservation under air cavity-free suspension hook and stage I silicone prosthesis implantation (SMALND) compared with routine MRM. Methods This was a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In recent years, many studies were trying to reduce the complications by improved procedures. Liu et al showed that compared with traditional mastoscopic modified radical mastectomy (MRM), MRM with skin nipple-areola preservation under air cavity-free suspension hook and stage I silicone prosthesis implantation (SMALND) had lower complication rates [ 25 ]. For robotic surgery, dissection with non-robotic scissors and then robotic dissection can reduce the skin complication rate than dissection with robotic scissors [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies were trying to reduce the complications by improved procedures. Liu et al showed that compared with traditional mastoscopic modified radical mastectomy (MRM), MRM with skin nipple-areola preservation under air cavity-free suspension hook and stage I silicone prosthesis implantation (SMALND) had lower complication rates [ 25 ]. For robotic surgery, dissection with non-robotic scissors and then robotic dissection can reduce the skin complication rate than dissection with robotic scissors [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this procedure, mechanical devices are used to raise and pull axillary surface skin to replace the space demanded by mastoscopic surgery. After a 10-mm Trocar incision, vessel forceps were used to make a blunt dissection and create a lacuna that could avoid the allergy caused by solute process 24 . The omission of injection of the solution into blood vessels reduces the harm to axillary soft tissue, blood vessels, and lymphatics caused by lipolysis.…”
Section: Discussionmentioning
confidence: 99%